ANALISYS OF PAPER RESISTANCE TWO PRODUCT MATTPAPER - Erry Tri Prabowo; Efnyta Muchtar; Yessy Yerta Situngkir (Kreator, 2021)
Paper is the most widely used print media, made with cellulose fibers derived from tree wood and non-fiber. The existence of paper is a tool that is quite important in human civilization and its needs continue to increase from year to year. The tear resistance of paper greatly affects the printing process. The value of tear resistance is influenced by several factors, namely the size of the fiber, besides that it is also influenced by the number of bonds between the fibers, grammar, humidity, moisture content, fiber direction, adhesive on the paper. The purpose of this final project is to determine the value of paper tear resistance which is better between two types of 120 gram Mattpaper paper products, namely New Victory Luxe and Nevia products and also to determine the effect of paper tear resistance on the printing process. The writing method used is descriptive method with data collection / observation, testing and literature techniques. Based on the results of the tear resistance test with the Elmendorf test method, which is to test the tear resistance of a paper, the tear resistance value of Nevia paper products is better than New Victory Luxe paper products.Keywords—Resistance, Paper, Mattpaper